A branch and bound algorithm to solve a two-machine no-wait flowshop scheduling problem with truncated learning function. Issue 2 (2nd April 2020) - Azizi, Vahid; Hu, Guiping
ABSTRACT: This paper addresses a two-machine no-wait flowshop problem with the effect of the truncated learning function of jobs whose actual processing times depend on their positions in the sequence. By considering truncated learning effect, the actual processing time of a job is a function of its position index in the schedule and a control parameter. In a production scenario with truncated learning effect, the actual processing time of a job will not be lower than a threshold when the number of processed jobs increases. We develop a branch and bound algorithm to minimize the makespan. A lower bound and a dominance property have been proposed to increase the speed of elimination process in the branch and bound algorithm.